Genetic Diversity Test of Various Javanese Local Sorghum Us-ing RAPD Molecular Markers - Utami, Erisa Putri; Hazmi, Muhammad; Murtiyaningsih, Hidayah (Universitas Muhammadiyah Jember, 2024)
Sorghum is one of the cereal crops that has good growth adaptation and production on dry land so that it has the potential to be developed in Indonesia. Besides being able to produce in dry areas, sorghum has a higher protein content compared to corn and cracked rice, but lower than wheat. Local sorghum used in this study included local Jember, local Demak, local Nganjuk, and local Majalengka. The level of genetic diversity of sorghum in Indonesia is still relatively low. Therefore, it is necessary to test the genetic diversity of sorghum with plant breeding. To obtain genetic diversity, this research conducted identification using RAPD molecular markers with 9 primers, namely OPA- 01, OPA-02, OPA-03, OPA-04, OPA-05, OPA- 06, OPA-11, OPA 17, and OPA 18. Based on the results of RAPD, the results of DNA bands were obtained which were continued with the NTSYSpc program to produce a kinship tree between local sorghum plants. From the results of the phylogenetic tree, it is known that the local sorghum of Majalengka and Lamongan have a parallel kinship, which means that the sorghum is genetically the same. Meanwhile, the genetic diversity of local sorghum in Jember and Demak is far compared to Lamongan and Majalengka. Nganjuk local sorghum has a genetic diversity line position in the middle (Jember, Demak) and (Majalengka, Nganjuk).